(untitled) (International Journal of Physiotherapy, 2024)
Background: Recently, there has been an increased interest in software-aided goniometric measurements in clinical establishments because of their uncomplicated availability and accuracy. This study evaluates the reliability of Kinovea software as a measurement tool for pelvic tilt in a sagittal plane. Methods: Ninety-five healthy people with a mean age of 20.67 ± 1.91, ninety-three females and two males, had reflective markers placed on the anatomical landmarks of ASIS and PSIS and were photographed with a tripod-mounted camera from 180 cm. The photos were taken thrice on both the right and left sides of the pelvis in the sagittal plane. They were then analyzed using Kinovea software to measure the pelvic tilt. The measured data were subjected to intra-rater reliability in two sessions at an interval of 24 hours. For inter-rater reliability, the second rater analyzed the coded photos of each subject on the fourth day. Both the raters were blinded to each other, and the subjects were blinded to the readings until the study was completed. Results: For intra-rater reliability, the results showed excellent reliability for the measurement of pelvic tilt on both sides of the pelvis between the first and second session (Cronbach’s alpha = 0.98 and ICC=0.98), and for inter-rater reliability showed significant agreements between the raters (Cronbach’s alpha value = 0.98 and ICC =0.98). Conclusion: Kinovea software is a highly reliable and promising tool for measuring pelvic tilt in the sagittal plane for posture analysis.